Assessing indigenous ureolytic bacteria isolated from Gua Damai limestone for microbially induced calcite precipitation (MICP) - Saad, Aljohani Waad Awdah; Fadzel, Nini Tasnim; Go, Rusea; Abdul Aziz, Nor Azwady; Mustafa, Muskhazli (Universitas Gadjah Mada, Faculty of Biology, 2025)
Low porosity and non-aggregated soil are significant global concerns, presenting substantial environmental hazards. This study determined the capacity of native ureolytic bacteria found in limestone to stabilise soil through the process of microbially induced calcite precipitation (MICP). Six pure bacterial isolates obtained from limestone in Gua Damai, Batu Caves, Selangor were qualitatively assessed for urease production. The isolate S4C4, identified as Bacillus tropicus strain NTF4, demonstrated the highest urease activity at 821.654 U mL-1. This isolate precipitated 37.15 ± 9 mg mL-1 of CaCO3 after 96 hours of incubation and XRD analysis confirmed the biocementation of organic soils treated by B. tropicus strain NTF4, primarily forming calcite and vaterites. Significant calcite polymorph presence in soil samples is attributed to a longer treatment duration which promotes crystal development and stability. Harnessing indigenous limestone ureolytic bacteria with high urease activity presents a promising avenue for green soil bio-stabilisation. This approach potentially unlocks sustainable and scalable applications of microbial-induced calcite precipitation (MICP) in large-scale geo-engineering projects.